An interval type-2 fuzzy enhanced best–worst method for the evaluation of ship diesel generator failures. (August 2022) - Yucesan, Melih; Başhan, Veysi; Demirel, Hakan; Gul, Muhammet
Highlights: This study proposes a new methodology called best-worst multi-criteria decision-making method enriched with interval type-2 fuzzy logic. A solid decision mechanism has been developed to prioritize generator failures. A new consistency index table is proposed for the proposed IT2FE-BWM. Abstract: The environmental destruction in our century necessitates the implementation of more safety-based rules and the strict implementation of failure analysis, especially in the maritime sector. The generator system, considered the ship's powerhouse, is expected to be ready and well-maintained for efficient and safe operations. This study proposes a new methodology to analyze ship generator failures. This method includes a version of the best-worst multi-criteria decision-making method enriched with interval type-2 fuzzy logic (IT2FE-BWM). Enrichment with interval type-2 fuzzy numbers shows that a parameter about how much the decision-maker trusts the pairwise comparisons are added to the model. Thus, a more sensitive methodology has been proposed for the confidence of the maritime sector evaluators. A solid decision mechanism has been developed to prioritize generator failures. In addition, a comparison study with some other BWM derivatives and a creative sensitivity analysis were added to this study and its robustness was tested.